PENERAPAN SUPERVISI AKADEMIK UNTUK MENINGKATKAN KEMAMPUAN GURU DALAM MERENCANAKAN DAN MELAKSANAKAN PEMBELAJARAN - Kemat Kemat Kemat (Manajer Pendididikan, 2016)
This aims study is to describe the implementations of both academic supervision and class observation techniques to enhance of planning and performing learning skill of SD Negeri1 Arga Makmur teachers in academic year 2013/2014. This is an action research scool (PTS) study conducted by two cycles in with five pers on acted as the subject having been determinated based on the result of pracycles observation, observation techniques were conducted to collect the data and quantitative descriptive analysis were used as data analysis.The study resulted that the implementation of both academic supervision and class observation techniques enhanced the planning and performing learning skill of SD Negeri 1 Arga Makmur teaches on odd semester in academic year 2013/2014.Keywords: academic supervision, planning, implementation, learning